Insulin and insulin-like growth factor 1 stimulate the phosphorylation on tyrosine of a 160 kDa cytosolic protein in 3T3-L1 adipocytes. - Madoff, D H (1988)
Insulin and IGF-1 (insulin-like growth factor 1) rapidly stimulate the phosphorylation on tyrosine of a 160 kDa cytosolic protein (pp160) in intact 3T3-L1 adipocytes. Half-maximal phosphorylation of pp160 is attained with either 4 nM-insulin or 20 nM-IGF-1. A semi-quantitative immunoblotting procedure using anti-phosphotyrosine antibody revealed that the insulin-stimulated 3T3-L1 adipocyte possesses approx. 3 x 10(5) and 0.6 x 10(5) phosphotyrosyl sites, respectively, in pp160 and insulin receptor beta-subunit. Removal of insulin from stimulated cells results in the rapid (within 15 min) loss of phosphate groups from tyrosyl residues in both pp160 and receptor beta-subunit. Whereas pp160 remains maximally phosphorylated on tyrosine for up to 60 min in the presence of 100 nM-insulin, IGF-1 at the same concentration induces only a transient response that is maximally 50% of that observed with insulin. pp160 is not phosphorylated on tyrosine in response to platelet-derived growth factor or epidermal growth factor. Although pp160 appears to be a soluble cytoplasmic protein, in the presence of 1 mM-ZnCl2 it becomes membrane-associated. In view of its apparent cytoplasmic localization and its inability to bind to either wheat-germ agglutinin or concanavalin A, pp160 does not appear to be a typical glycoprotein growth-factor receptor. Our results suggest that pp160 may be a physiologically important cellular substrate of the insulin-receptor tyrosine kinase in the intact 3T3-L1 adipocyte.